Kazakhstan’s engagement in international climate agreements: legal dimensions and domestic implementation - Shoshayeva, L.S.; Nukusheva, A.A. (Bulletin of the Karaganda University “Law Series”, 2025)
Majority of states, including the Republic of Kazakhstan, face the need to transform their economic and legal models in response to the growing climate and environmental challenges. The endorsement of key strategic frameworks, the Strategy for Achieving Carbon Neutrality by 2060 and the updated Nationally Determined Contribution (UNDC) under the Paris agreement underscores the importance of legal analysis of climate policy and evaluation of the effectiveness of implemented mechanisms. The purpose of this study is to conduct a comprehensive analysis of national and international legislation in the field of climate change, as well as to examine the positions and materials of leading international organizations, including the Conferences of the Parties (COP) to the UNFCCC and the Climate Ambition Summit. The methodological framework includes systematic, comparative and formal legal methods, as well as political and legal analysis, which made it possible to assess the state of the legislative framework and identify key legal challenges. The study identified the main institutional and regulatory barriers hindering the implementation of the climate agenda: the lack of clear mechanisms for implementing strategies, fragmented legal regulation, weak coordination between government agencies, and the conflict between climate policy and current economic priorities, in particular in the field of hydrocarbon production. It is concluded that it is necessary to improve national legislation and strengthen the institutional foundations of climate governance.